Analisa Hubungan antara Size, Product Life Cycle, dan Market Position dengan Penggunaan Balanced Scorecard pada Sektor Ritel di Surabaya - Sari, Christina Permata (Business Accounting Review, 2013)
Recently, the competition in business is very sharp. A competition in the business environment has encouraged retailers to improve their quality in order to increase organization performance. Therefore, the retail companies require an alternative performance assessment by using the balanced scorecard in a more comprehensive, accurate, and scalable. The study aimed to examine the relationship among organization size, product life cycle, and market position and the balanced scorecard usage in retail sector in Surabaya. Using financial and nonfinancial measures, the balanced scorecard appraises four dimensions of performance: financial, customers, internal business process, and learning and growth aspects. The data were collected by distributing questionnaires to the managers or owners whose businesses in some of the retail companies in Surabaya. The criteria of the established retail companies were the food retailers and general merchandise retailers that have managers or owners who have worked at least for six months. The study shown that there was a relationship among the retail major, products at the early stage, and strong position in the market and the use of the balanced scorecard. The study also shown that the highest of balanced scorecard usage was on the learning and growth perspective, which amounted to 25.36%.